Effect of the ozonation pretreatment on biogas production from waste activated sludge of tehran wastewater treatment plant. (September 2021) - Hodaei, Mahdi; Ghasemi, Shahnaz; Khosravi, Arash; Vossoughi, Manouchehr
1. Abstract: In this study, the ozonation impact on anaerobic digestion of wasted thickened activated sludge of Tehran wastewater treatment plant has been investigated. Regarding that, the thickened activated sludge, a final solid waste of treatment plants, was subjected to ozonation pretreatment to evaluate its characteristics. Three major sludge characteristics were considered for investigating ozonation effects on anaerobic digestion. A comparison of two different ozone doses, i.e., 0.05 and 0.1 gO3 g −1 TS was performed for short-term (10 days) and long-term (30 days) sludge retention times. Furthermore, biogas production, sludge composition, dewaterability, and energy balancing, were studied during the periods mentioned above. The results show that the lower ozone dose has an acceptable performance in a short-term operation for all parameters except energy balance which was negative in all the scenarios. Higher ozone dosage not only decreased biogas production and volatile solids reduction but also significantly increased the energy demand of the system. In addition, a longer retention time reduced the effectiveness of the ozone pretreatment during that time. Eventually, the feasibility of ozone pretreatment capacity for sustainable management of different sludge from economic and technological perspectives can be evaluated by further assessing this case study. Graphical abstract: Image 1 Highlights: Comparative investigation of different ozone doses on activated sludge composition. Performance evaluation of ozonation during short and long sludge retention times. Study of ozonation effect on biogas production and sludge dewaterability. Assessment of ozone impact on energy production, consumption, and energy balancing.